KONSEP TOLERANSI ANTAR UMAT BERAGAMA PERSPEKTIF SYAIKH NAWAWI AL-BANTANI DALAM TAFSIR MARAH LABID - Fatcholli, Imadul Haq (Reflektika, 2019)
This paper explains the ethics of the Qur'an towards non-Muslims. Islam as a peaceful religion is often accused and harassed by Islamic haters. The allegations and abuse are contained in several articles, journals, and books. Islam is not what they are accused of. Even Islam countered these accusations with very tolerant teachings. Islam teaches its people to respect the ummah of other religions, forbids them to insult other religions, denounces their worship, or forces non-Muslims to embrace Islam, even Islam teaches its ummah to recognize non-Muslims as brothers. This is the respect for Islam against non-Muslims. So in this case one of the firm figures of Shaykh Nawawi al-bantani offers good and true religious tolerance. Shaykh Nawawi> al-Banta>ni> was born in 1230 A.D. But some state that Shaykh Nawawi> was born in 1814 AD and died in Mecca on 25 Syawwal 1340 AD/ 1897 AD. In this journal the author describes how the nature of religious tolerance and its limitations and in this journal uses interpretation methods and descriptions using this type of research library research with descriptive analysis.